The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11099-013-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Leaf morphological and ultrastructural performance of eggplant (Solanum melongena L.) in response to water stress

Abstract: The effects of water stress on leaf surface morphology (stomatal density, size, and trichome density of both adaxial and abaxial surfaces) and leaf ultrastructure (chloroplasts, mitochondria, and cell nuclei) of eggplant (Solanum melongena L.) were investigated in this study. Higher stomata and trichome densities were observed on abaxial surface compared with the adaxial surface. Compared with well watered (WW) plants, the stomata and trichome density of the abaxial surface increased by 20.39% and 26.23% under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 32 publications
2
24
1
1
Order By: Relevance
“…These phenomena are similar to previous observations on tomato (Gay and Hurd 1975), Amaranthus tricolor (Ren et al 2004), andSorbus (Č aňová et al 2012). Irrespective of developmental stage, severe drought, but not medium drought, significantly increased stomatal density and significantly reduced stomatal size in maize, consistent with numerous previous studies (Bosabalidis and Kofidis 2002;Dunlap and Stettler 2001;Fu et al 2013;Pearce et al 2005), but contradictory to the results of Xu et al (2003) and Xu and Zhou (2008). Small stomata could maintain the pores opening with lower guard-cell turgor pressures compared with larger stomata (Spence et al 1986).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These phenomena are similar to previous observations on tomato (Gay and Hurd 1975), Amaranthus tricolor (Ren et al 2004), andSorbus (Č aňová et al 2012). Irrespective of developmental stage, severe drought, but not medium drought, significantly increased stomatal density and significantly reduced stomatal size in maize, consistent with numerous previous studies (Bosabalidis and Kofidis 2002;Dunlap and Stettler 2001;Fu et al 2013;Pearce et al 2005), but contradictory to the results of Xu et al (2003) and Xu and Zhou (2008). Small stomata could maintain the pores opening with lower guard-cell turgor pressures compared with larger stomata (Spence et al 1986).…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies on the response of stomatal density to soil drought reported inconsistent results. Under drought stress, leaf stomatal density increased in wheat (Quarrie and Jones 1977), Populus trichocarpa (Dunlap and Stettler 2001), olive (Bosabalidis and Kofidis 2002), and Solanum melongena (Fu et al 2013) but decreased in ginger (Xu et al 2003) and increased under moderate water deficit in Leymus chinensis but decreased under severe water deficit (Xu and Zhou 2008). Additionally, in previous reports the correlations between stomatal density and gas exchange were also not consistent.…”
Section: Introductionmentioning
confidence: 93%
“…We observed a higher TD in ILs 4‐1 and 11‐3 under WD conditions compared with WW conditions (Figure a). Increases in TD with herbivore and water stress have been reported previously in several species (Traw and Bergelson, ; Bjorkman et al ., ; Fu et al ., ), as part of the adaptive stress response. In fact, transcriptomic studies in water‐stressed Arabidopsis thaliana plants showed an upregulation of genes related to trichome initiation and morphogenesis (TT8, BRICK1, KAK), but not of genes involved in stomatal initiation (Bechtold et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In Citrullus lanatus (watermelon), wild, drought‐tolerant genotypes have increased trichome density compared with domesticated, drought‐sensitive varieties (Mo et al ., ). In addition, trichome formation is increased in plants grown under water stress, such as Hordeum vulgare (barley; Liu and Liu, ), Solanum melongena (aubergine; Fu et al ., ) and Olea europaea (olive; Boughalleb and Hajlaoui, ). Trichomes may limit water loss by transpiration through an increase of the leaf–air boundary layer resistance (Palliotti et al ., ; Guerfel et al ., ; Mo et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have focused on examining trichome characteristic responses to soil water deficit in effort to determine whether (and to what extent,) the trichome enhances drought resistance ability in plants (Gianoli and Gonz alez-Teuber 2005;Huttunen et al 2010;Meng et al 2014). Trichome density is likely a plastic adaptive pattern to drought, on account of its barrier effect against the influence of CO 2 and H 2 O exchange, which reduces excessive transpiration and photoinhibition (Pallioti et al 1994;Gianoli and Gonz alez-Teuber 2005;Fu et al 2013). Trichomes also can reduce the plant's solar radiation absorption and decrease its temperature by increasing the leaf surface boundary layer, further protecting the plant from drought (Schreuder et al 2001).…”
Section: Introductionmentioning
confidence: 99%